2016
DOI: 10.1007/s11031-016-9574-6
|View full text |Cite
|
Sign up to set email alerts
|

Do you get what you pay for? Sales incentives and implications for motivation and changes in turnover intention and work effort

Abstract: This study investigated relations between pay-for-performance incentives designed to vary in instrumentality (annual pay-for-performance, quarterly pay-for-performance, and base pay level) and employee outcomes (self-reported work effort and turnover intention) in a longitudinal study spanning more than two years. After controlling for perceived instrumentality, merit pay increase, and the initial values of the dependent variables, the amount of base pay was positively related to work effort and negatively rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 67 publications
5
87
0
4
Order By: Relevance
“…Finally, it is interesting to note that – even though we did not set out to test a direct relationship between bonus level and intrinsic motivation – bonus level was negatively related to changes in intrinsic motivation when associated with low perceived manager discretion. This result is interesting because annual PFIP is generally assumed to have a lower level of performance contingency, which is less salient and therefore less undermining (Cerasoli et al, ; Deci et al, ), although Kuvaas and colleagues () found, similar to us, that annual PFIP negatively predicted intrinsic motivation. We anticipate that our findings are because the bonus associated with low perceived manager discretion is perceived to represent an incomplete evaluation of performance (Bol, ), making the outcome more salient (Cerasoli et al, ), which could be seen as controlling (Ryan et al, ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Finally, it is interesting to note that – even though we did not set out to test a direct relationship between bonus level and intrinsic motivation – bonus level was negatively related to changes in intrinsic motivation when associated with low perceived manager discretion. This result is interesting because annual PFIP is generally assumed to have a lower level of performance contingency, which is less salient and therefore less undermining (Cerasoli et al, ; Deci et al, ), although Kuvaas and colleagues () found, similar to us, that annual PFIP negatively predicted intrinsic motivation. We anticipate that our findings are because the bonus associated with low perceived manager discretion is perceived to represent an incomplete evaluation of performance (Bol, ), making the outcome more salient (Cerasoli et al, ), which could be seen as controlling (Ryan et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…When informational cues are more salient, the task itself becomes the perceived cause of the action, maintaining or enhancing intrinsic motivation (Ryan, ; Thibault‐Landry et al, ). This perspective is supported by empirical research which suggests, for example, that base pay level – which represents a low contingency incentive, which is therefore more informational – is either directly (Kuvaas, ; Kuvaas et al, ) or indirectly (Olafsen et al, ) positively related to autonomous motivation (Gagné and Deci, ). Further, in explicitly exploring the functional significance that individuals attach to incentives, Thibault‐Landry and colleagues () found in two cross‐sectional field surveys that individuals reported higher levels of autonomous motivation when they believed their incentives to be informational.…”
Section: Theory and Hypothesesmentioning
confidence: 93%
“…They are also extensively used in other contexts, including society at large when, for example, governments offer tax-deduction incentives to increase charitable donations or premiums for recycling behaviors that protect the environment, or again when criminal sentences are reduced for an informant's helpful information within the judicial system (Underhill, 2016). Within organizations, MCT has been adopted to investigate the effect of extrinsic rewards on intrinsic motivation in relation to several employee outcomes such as, for example, work effort (Dickinson & Villeval, 2008;Irlenbusch & Sliwka, 2005;Kuvaas, Buch, Gagné, Dysvik, & Forest, 2016), commitment and engagement (Putra et al, 2017), burnout and turnover (Kuvaas et al, 2017), and the tendency to move from one sector to another (Georgellis, Iossa, & Tabvuma, 2010).…”
Section: Mct and Organizational Innovationmentioning
confidence: 99%
“…Finally, external regulation represents engaging in an activity in order to obtain a social (e.g., approval) or material (e.g., bonus) reward or to avoid a social (e.g., criticism) or material (e.g., job loss) punishment. Because this type of motivation is often weakly associated with work performance and effort (e.g., Gagné et al, ; Kuvaas, Buch, Gagné, & Dysvik, ), Gagné () proposed that this type of motivation would be associated with minimally sanctioned sharing that would consequently be less frequent and of lower quality. Research so far has supported this by showing that external regulation was less positively associated with knowledge sharing than intrinsic motivation (Andreeva & Sergeeva, ).…”
Section: Introductionmentioning
confidence: 99%